Peri‐transplant clostridium difficile infections in patients undergoing allogeneic hematopoietic progenitor cell transplant. Issue 3 (22nd February 2016) - Agha, Aya; Sehgal, Alison; Lim, Matthew J.; Weber, David; Hou, Jing‐Zhou; Farah, Rafic; Raptis, Anastasios; Im, Annie; Dorritie, Kathleen; Marks, Stanley; Agha, Mounzer; Lim, Seah H.
Abstract : Clostridium difficile infections (CDI) remain the leading cause of infectious diarrhea among hospitalized patients in this country. Patients with hematologic malignancies, especially those who undergo hematopoietic progenitor cell transplants are particularly at risk for developing CDI. One hundred and forty seven consecutive allogeneic hematopoietic progenitor cell transplants were analyzed for peri‐transplant Clostridium difficile infections (PT‐CDI). Sixteen patients (11%) developed PT‐CDI (Median time = 7 days after transplant). The probability for developing PT‐CDI during the peri‐transplant period was 12.3%. History of CDI was strongly associated with the development of PT‐CDI ( P  = 0.008) (OR = 5.48) ( P  = 0.017). These patients also developed PT‐CDI much earlier than in those without a history (median 1 day vs . 8 days, P  = 0.03). The probability for developing PT‐CDI for those with a history was 39%. There was a trend toward significance ( P  = 0.065) between matched related donor grafts and the development of PT‐CDI (OR = 0.245) ( P  = 0.08). Age, sex, diagnosis, transplant preparative regimens, Graft‐versus‐host disease (GVHD) prophylaxis, grade 3/4 acute GVHD, or use of antimicrobials within 8 weeks of transplant were not associated with PT‐CDI. Non‐CDI‐related deaths occurred in one patient in the PT‐CDI group and nine in the group without PT‐CDI. In the remaining 139 patients, the length of hospital stay for those with PT‐CDI was significantly longer than those without (mean 27 days vs . 22 days; P  = 0.02). Am. J. Hematol. 91:291–294, 2016. © 2015 Wiley Periodicals, Inc.